Communicative styles of English students at the State University of Makassar - Mahmud, Murni (Penerbit Universiti Kebangsaan Malaysia, 2017)
Communication has a crucial function in English language teaching because failure in communication will result in unsuccessful process. Therefore, it is important to investigate the styles of communication used in the classroom, especially by students. The focus of this paper is to explore the expressions used by a group of students to communicate in the classroom. This paper is based on a study conducted in 2015 at the State University of Makassar, South Sulawesi, Indonesia. This study focused on two English classes which employed classroom presentations as the learning strategy. To collect data, the researcher recorded the classroom presentations of the two classes. Twelve recordings from twelve groups of students were obtained, transcribed, and analyzed by using discourse analysis approach. The communicative styles used by the students were discussed based on the communication strategies of Dörnyei and Scott (1997) and the students’ talk was analyzed based on Brown’s FLINT system (2000). Findings show that students employed various styles to communicate in the classroom presentations. Their communicative styles can be in the form of speech acts, discourse markers, language choices, address terms, and the inclusion of regional terms derived from the Bugis-Makassar language such as the pronoun - ko and softeners -mi and -ji. Findings of this study are relevant in the development of English language teaching, particularly in effort to create effective classroom interaction.